2016
DOI: 10.1148/radiol.2015150013
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy for Breast Cancer: Functional Tumor Volume by MR Imaging Predicts Recurrence-free Survival—Results from the ACRIN 6657/CALGB 150007 I-SPY 1 TRIAL

Abstract: ).q RSNA, 2015 Purpose:To evaluate volumetric magnetic resonance (MR) imaging for predicting recurrence-free survival (RFS) after neoadjuvant chemotherapy (NACT) of breast cancer and to consider its predictive performance relative to pathologic complete response (PCR). Materials and Methods:This HIPAA-compliant prospective multicenter study was approved by institutional review boards with written informed consent. Women with breast tumors 3 cm or larger scheduled for NACT underwent dynamic contrastenhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
202
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(213 citation statements)
references
References 32 publications
10
202
0
1
Order By: Relevance
“…Our findings are supported by results of the I-SPY study, showing an association with tumour volume at end-of-treatment MRI and recurrence-free survival [23]. The prognostic value of rCR is an exploratory finding and must be confirmed in independent series.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings are supported by results of the I-SPY study, showing an association with tumour volume at end-of-treatment MRI and recurrence-free survival [23]. The prognostic value of rCR is an exploratory finding and must be confirmed in independent series.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown that smaller functional tumor volume and lower BPE around the tumor are associated with superior survival (38) and lower risk of recurrence in breast cancer (26), respectively. As luminal A cancer is known to have the best prognosis among all four subtypes, this lends support for our findings here.…”
Section: Discussionmentioning
confidence: 99%
“…This is different from previous studies (26,27) that calculate the absolute signal enhancement or its ratio of background parenchyma, which may be prone to MR signal artifacts or variations in image acquisition protocols. We believe that volume-based measurements are more robust to such variations (38) and that they are more closely related to how radiologists observe and interpret BPE on MR imaging, as suggested in BIRADS (29). …”
Section: Discussionmentioning
confidence: 99%
“…Breast magnetic resonance imaging (MRI) combined with mammography has been reported to be 90% to 100% sensitive in detecting breast cancer. Its usefulness has been reported not only in high-risk screening but also in pre-operative examination, evaluation of neoadjuvant chemotherapy response, and post-operative screening (2)(3)(4)(5). The use of breast MRI has been rapidly growing in Korea for the last 10 years.…”
Section: Introductionmentioning
confidence: 99%